Analisis Pelatihan, Pengembangan, dan Teknologi Informasi Terhadap Kinerja Karyawan Pada KPN ”JAYA” Guru SDN Raba Kota Bima - Aan Hidayat; Mulyadin Mulyadin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to determine the effect of training, development, and information technology on employee performance at KPN "Jaya" Guru SDN Raba. The population is 45 employees and the sample is 45 employees and the research is associative. Data collection techniques are observation, and filling out questionnaires, and literature study. The independent and dependent variables are the variables used in this study. The independent variables are training (X1), development (X2), and information technology (X3) and the dependent variable is employee performance (Y). The analysis technique uses quantitative analysis, namely multiple regression analysis, correlation coefficient, and determination coefficient. hypothesis testing using t test. the results of hypothesis testing using t test obtained tcount Variable X1 = (3.775) Variable X2 = (2.800) Variable X3 = (2.845) is greater than ttable (2.016) then it can be concluded that there is an influence between training, development, and information technology on employee performance at KPN “Jaya” Guru SDN Raba